A new generalization of α-type almost-F-contractions and α-type F-Suzuki contractions in metric spaces and their fixed point theorems - Taheri, A.; Farajzadeh, A.P. (Carpathian Mathematical Publications, 2019)
In this paper a new generalization of α-type almost-F-contractions and an extension of α-type F-Suzuki contractions are given. Moreover, some new fixed point theorems of them are discussed. Some examples and applications in order to illustrate the main results are presented. The results of this article can be considered as improvements of some well-known results appeared in the literature.